An Adaptive Wireless Droop Control with Adaptive Virtual Resistance for Power Sharing Management in MTDC Grid - Hasan Alrajhi; Ahmed Al-Zahrani; Syed A. Raza; Fahad Al-Shareef (Energies)
This paper presents an adaptive wireless droop control scheme that uses an adaptive virtual resistance to regulate the DC voltage and control the active power. The proposed methodology is implemented to address the power mismatch problem in a fixed-droop control for multi-terminal HVDC (MT-HVDC or MTDC) systems. Each inverter calculates available power and adjusts its output power accordingly while adapting the virtual resistance to mimic the behavior of a mesh system that is based on loading effects. The main objective of this methodology is to increase the reliability of the MTDC system by eliminating the need for fast communication links and ensuring proper power sharing between inverters. Additionally, this communication-free scheme includes a power management algorithm that controls power sharing during peak hours of the inverters among the rectifiers as per mutual agreements between the operators to mitigate the risk of a system overload and optimize the power sharing. A simulation of a five-terminal mesh MTDC system has been verified by using PSCAD/EMTDC to validate the performance and effectiveness of the proposed method. The results show the flexibility and feasibility of the proposed control method in three different modes.